Technique of defining the electric resistance of the IC contact pads - Hotra, Zenon; Dyachok, Dmytro; Lob, Yaroslav; Semenyuk, Anatoliy (Видавництво Львівської політехніки, 2010)
There are presented the technique and results of defining the electric resistance value of the IC microcontact connection contact pads.
Keywords: integral circuit; contact pad; resistance